The impact of visual functions on athletes' results and methods of their improvements - I. B. Medvedev; M. V. Gusakov; M. U. Borisova; T. I. Blankova; N. I. Medvedeva; N. N. Dergacheva (National Electronic Information Consortium (NEICON), 2023)
Regardless of the sport, maintaining and improvement of visual functions in athletes act an important role in achieving personal records.In this article, the interrelationships between sports results and the state of visual functions were determined, as well as devices and methods were analyzed, thanks to which it is possible to improve functions of the visual analyzer.